Hubungan Melasma Dengan Tingkat Kualitas Hidup Pada Wanita - Said, Reza Nur (2016)
Background: Melasma is hyperpigmentation, generally symmetrical, macular form uneven light brown to dark brown, and most frequently noticed on sun-exposed areas of the face, especially the cheeks, forehead, upper lip, nose, and chin. Psychologically, melasma potentially interfere appearance of someone and lead to low self-esteem that can reduce productivity, self-esteem, and social functioning for the patients. Objective:To determine the correlationbetweenmelasmawith the level ofquality of lifein women. Methods: This study used observational method with cross sectional study design. Sample size of this study was 50 womenaged30-44yearswho suffer frommelasmaand who didn'tsuffer frommelasmainTurirejoVillage, District Jepon, Blora. Sampling technique used purposive sampling. Datawere analyzedwithChi-square using SPSS programversion 17.0. Result: The level of quality of life in patients with melasma 16% poor, 36% low, 24% moderate, 24% good. Statistical test result p value = 0.000, so it can be concluded that there is a significant corellation between melasma with the level of quality of life.Conclusion: There is a corellation between melasma with the level of quality of life in women with the highest levels of quality of life is lowquality of lifewith a percentage of36%.